Rehabilitation examination, rehabilitation diagnosis and rehabilitation program for patients with breast cancer - Anastasia Shepel; Anatolij Levkov (Фізична реабілітація та рекреаційно-оздоровчі технології, 2022)
In the general structure of lead malignant new formations of skin. Such diagnosis in 2020 is put to 188 298 Ukrainians. Does not almost yield to the “leader” of chasse of mammary gland. The amount of оwith this diagnosis in 2020 grew to 157 274 persons, that on 4500 cases more than in 2019. The general height of chasse of breasts was a bit slowed. In 2019 he presented 5600, and in 2018 – 5200. But a similar situation, probably, – the result of the limitations related to the quarantine, that influenced on diagnostics. The purpose of the study: to investigate the problem of rehabilitation of patients with breast cancer, to form a step-by-step plan for the rehabilitation of patients, to describe the most complete recovery, prevention of complications and recurrences. Methods: analysis of scientific and methodological literature, synthesis of acquired knowledge, method of comparison, deduction, generalization and abstraction.